Upaya Meningkatkan Hasil Belajar Siswa dalam Pembelajaran IPS melalui Model Teams Games Tournament (TGT) Kelas VIII MTsN 2 Kota Kediri - Lathifa, Akhliyash Dina (Maliki Interdisciplinary Journal, 2025)
By implementing the Teams Games Tournament (TGT) cooperative learning model in class VIII-N MTsN 2 Kota Kediri, this study seeks to enhance students’ learning outcomes in Social Studies (IPS). The low learning outcomes of students in social studies classes, which are brought on by a lack of diversity in teaching approaches and the predominance of one approach that renders pupils inert, serve as the backdrop for this study. 36 students served as the subjects of this two-cycle Classroom Action Research (PTK) study. There were phases for preparation, activity, observation, and reflection in every cycle. Learning outcome tests, observation sheets, and recordkeeping were the instruments utilized. The findings demonstrated that student learning outcomes improved with each phase. While just 33.33% of students met the KKM (minimum completion requirement) in the pre-cycle. Cycle I saw a rise to 80.56%, and Cycle II had a 100% increase. It was discovered that the TGT model was useful in boosting student interest in learning, engagement, and attaining the best possible learning results. Therefore, when learning social studies, the TGT learning model can be utilized as an inventive and enjoyable alternative learning method.